Effects of calcium silicate cements on neuronal conductivity - Derya Deniz-Sungur; Mehmet Ali Onur; Esin Akbay; Gamze Tan; Fügen Daglı-Comert; Taner Cem Sayın (Restorative Dentistry & Endodontics, 2022)
ObjectivesThis study evaluated alterations in neuronal conductivity related to calcium silicate cements (CSCs) by investigating compound action potentials (cAPs) in rat sciatic nerves.Materials and MethodsSciatic nerves were placed in a Tyrode bath and cAPs were recorded before, during, and after the application of test materials for 60-minute control, application, and recovery measurements, respectively. Freshly prepared ProRoot MTA, MTA Angelus, Biodentine, Endosequence RRM-Putty, BioAggregate, and RetroMTA were directly applied onto the nerves. Biopac LabPro version 3.7 was used to record and analyze cAPs. The data were statistically analyzed.ResultsNone of the CSCs totally blocked cAPs. RetroMTA, Biodentine, and MTA Angelus caused no significant alteration in cAPs (p > 0.05). Significantly lower cAPs were observed in recovery measurements for BioAggregate than in the control condition (p < 0.05). ProRoot MTA significantly but transiently reduced cAPs in the application period compared to the control period (p < 0.05). Endosequence RRM-Putty significantly reduced cAPs.ConclusionsVarious CSCs may alter cAPs to some extent, but none of the CSCs irreversibly blocked them. The usage of fast-setting CSCs during apexification or regeneration of immature teeth seems safer than slow-setting CSCs due to their more favorable neuronal effects.